Estilos de aprendizagem e estratégias cognitivas: em busca de maior autonomia na aprendizagem de língua estrangeira. - Cardoso, Lídia Amélia de Barros (2007)
This dissertation analyses the learning process of a group of seven American undergraduate students learning Portuguese as a foreign language. The research carried identified their learning styles through the Index of Learning Styles (ILS), proposed by Richard Felder (1998), and their cognitive strategies based on the Strategy Inventory for Language Learning (SILL) by Rebecca Oxford (1990). The initial hypothesis was that from the design of material and methodological procedures which tried to accommodate both learning styles and the development of cognitive learning strategies their linguistic skills and communicative competence would be significantly optimized. The results indicated that 86% of the group attained best proficiency and more autonomy. The evidence is that the students who used a bigger number of strategies and those who created their own strategies improved their proficiency significantly. The main pedagogical implication is that the use of learning strategies should be considered a key factor in language learning.